Role of hormones and neurosteroids in epileptogenesis - Reddy, D Samba (Frontiers in Cellular Neuroscience, 2013)
This article describes the emerging evidence of hormonal influence on epileptogenesis, which is a process whereby a brain becomes progressively epileptic due to an initial precipitating event of diverse origin such as brain injury, stroke, infection, or prolonged seizures. The molecular mechanisms underlying the development of epilepsy are poorly understood. Neuroinflammation and neurodegeneration appear to trigger epileptogenesis. There is an intense search for drugs that truly prevent the development of epilepsy in people at risk. Hormones play an important role in children and adults with epilepsy. Corticosteroids, progesterone, estrogens, and neurosteroids have been shown to affect seizure activity in animal models and in clinical studies. However, the impact of hormones on epileptogenesis has not been investigated widely. There is emerging new evidence that progesterone, neurosteroids, and endogenous hormones may play a role in regulating the epileptogenesis. Corticosterone has excitatory effects and triggers epileptogenesis in animal models. Progesterone has disease-modifying activity in epileptogenic models. The antiepileptogenic effect of progesterone has been attributed to its conversion to neurosteroids, which binds to GABA-A receptors and enhances phasic and tonic inhibition in the brain. Neurosteroids are robust anticonvulsants. There is pilot evidence that neurosteroids may have antiepileptogenic properties. Future studies may generate new insight on the disease-modifying potential of hormonal agents and neurosteroids in epileptogenesis.